Applying the input-output price model to identify inflation processes - Michał Przybyliński; Artur Gorzałczyński (Journal of Economic Structures, 2022)
We try to examine the potential of input-output price model to identify mechanisms of price formation and transmission. Contrary to previous research that focused on overcoming the specific limitations of the model, we test its overall performance. In the presented study, the historical values of the commonly used consumer price index were decomposed according to the classic input-output price model for an open economy. A sequence of ex post simulations under various assumptions was used to identify the sources of inflation. This study required the use of input-output tables in current and previous year's prices. The proposed method of decomposition might be a starting point to create a framework for studying different aspects of inflation process.
Keywords: C67; E31; E37; 330; Cost-push price formation; Exchange rate pass-through; Inflation; Input-output price model